La remuneración en garantía - Mejorada Chauca, Martín (2014)
Credit is an asset of the creditor that can be transferred, allowing event the constitutionof a security on it. Now, despite the fact that the remuneration the worker perceives is also a credit, the Law of Movable Collaterals has expressly excluded security possibilities on it, limiting the property right of the worker and economically damaging him. Is this right?In this article, the author develops the answer to this question, through a systematic interpretation of Peruvian legislation and the credit figure as an object of movable collateral.